Maternal mental health and child well-being in Nigeria: A systematic review. Issue 1 (April 2021) - Jidong, Dung Ezekiel; Husain, Nusrat; Ike, Tarela J; Murshed, Maisha; Pwajok, Juliet Y; Roche, Ayesha; Karick, Haruna; Dagona, Zubairu K; Karuri, Gloria S; Francis, Christopher; Mwankon, Shadrack B; Nyam, Pam P
Maternal mental health distress has a disease burden of severe adverse effects for both mother and child. This review identified maternal mental health concerns, their impact on child growth and the current practice of maternal healthcare for both mothers and their children in Nigeria. The Population, phenomenon of Interest and Context (PICo) model was adopted to formulate the review strategy, and five databases were searched for published articles between 1999 and 2019. Databases include Scopus, PubMed, ProQuest, Applied Social Science Index and Abstracts and Web of Science. Boolean operators (AND/OR/NOT) helped to ensure rigorous use of search terms which include 'maternal', 'pre/peri/postnatal', 'mental health', 'mental illness', 'disorders', 'intervention, ' 'Nigeria', 'child', 'infant growth', and 'wellbeing'. Thirty-four studies met the inclusion criteria, and extracted data were qualitatively synthesised and analysed thematically. Five themes emerged. These include (i) marital difficulties, (ii) relationship status of the mother, (iii) child's gender, (iv) mode of child delivery and (v) child growth and development. The review showed a significant paucity of literature on the impact of specific maternal mental health problems on child physical growth and cognitive development. We concluded that culturally appropriate and evidence-based psychological interventions for maternal mental health problems would benefit Nigerian indigenous mothers. Therefore, the study recommends randomised controlled trials that are culturally appropriate and cost-effective for distressed mothers with children.